1986
DOI: 10.1159/000124463
|View full text |Cite
|
Sign up to set email alerts
|

Different Opioid Mechanisms Are Involved in the Modulation of ACTH and Gonadotrophin Release in Man

Abstract: Both the pituitary-adrenal axis and the pituitary-gonadal axis are under the tonic inhibitory control of endogenous opioid peptides in man. However, the precise opioid receptor involved in the modulation of these hormones remains unknown. The effect of a dose of intravenous naloxone on serum levels of luteinising hormone (LH), follicle-stimulating hormone (FSH) and plasma cortisol was therefore investigated in ten normal subjects. In the male subjects, naloxone at a dose of 25 µg/kg caused a significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 26 publications
6
48
1
Order By: Relevance
“…In normal subjects, the infusion of naloxone elevates plasma ACTH and cortisol but only if given in high doses, above 10 -15 mg (1,3,32,36,39,40). In agreement with these data, we found that the infusion of approximately 9 mg naloxone, over 6 1 ⁄2 h, had no effect on plasma ACTH levels during normocortisolism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In normal subjects, the infusion of naloxone elevates plasma ACTH and cortisol but only if given in high doses, above 10 -15 mg (1,3,32,36,39,40). In agreement with these data, we found that the infusion of approximately 9 mg naloxone, over 6 1 ⁄2 h, had no effect on plasma ACTH levels during normocortisolism.…”
Section: Discussionsupporting
confidence: 87%
“…Several explanations may account for this discrepancy: exogenous opiates may show pharmacological and not physiological effects; and apparently, some opiates have agonist activity, as well as antagonist activity (13). Furthermore, opiates differ in their relative affinity for different receptor subtypes (13,32), and the in vivo function of endogenous opioids may involve receptors that are relatively insensitive to naloxone (3,9,13,(33)(34)(35). Naloxone is a competitive inhibitor of opiate receptors; but in low doses, it has the highest affinity for -and ⑀-receptors, whereas relatively large doses are required to block the ␦-and -receptors (3,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, opioids are well known to be a cause of hypogonadotropic hypogonadism [5]. Similar results has been observed in methadone addicts, where previous studies observed decreased plasma cortisol levels as well as an absence of Adrenocorticotrophin Hormone (ACTH) response to CASE REPORT ity swelling with pitting edema, and vinous red striaes on abdomen for one month.…”
Section: Introductionsupporting
confidence: 67%
“…The restraint on LH release is predominantly mediated through central inhibition of hypothalamic GnRH secretion (18). Taking into account the receptor subtypes, PRL is preferentially activated by ⑀-receptors, TSH by -receptors, and ACTH probably by ␦-or -receptors, whereas the inhibitory control of LH involves ⑀-receptors (19,20). The receptors involved in GH stimulation remain unclear.…”
Section: Discussionmentioning
confidence: 99%